2015
DOI: 10.3343/alm.2015.35.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxocariasis and Its Clinical Implications in Gwangju and Jeonnam-province, Korea

Abstract: We investigated the seroepidemiological, clinical, and laboratory characteristics of patients suspected to have toxocariasis in Gwangju and Jeonnam-province, Korea. In total, 228 specimens were analyzed for anti-Toxocara canis IgG at two university hospitals from 2010 to 2012. The overall seropositive rate was 67.1%, and the seropositive rates among the eosinophilic and non-eosinophilic groups were 76.1% (105/138) and 53.3% (48/90), respectively. Risk factors for eosinophilia and toxocariasis were male sex (od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Various studies have suggested that geographical location, socioeconomical status, contact with soil, dog, and cat, age, sex, pica, and ingestion of raw cow liver or meat are the most important risk factors for acquiring the disease (Campos Júnior et al 2003;Fillaux et al 2007;Kwon et al 2017;Kwon et al 2011). Eosinophilia in peripheral blood occurs in allergic diseases and cancers and is commonly found in tissue-invading parasites (Merdin et al 2016;Won et al 2015); VLM is often complicated by blood eosinophilia (Van Den Broucke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have suggested that geographical location, socioeconomical status, contact with soil, dog, and cat, age, sex, pica, and ingestion of raw cow liver or meat are the most important risk factors for acquiring the disease (Campos Júnior et al 2003;Fillaux et al 2007;Kwon et al 2017;Kwon et al 2011). Eosinophilia in peripheral blood occurs in allergic diseases and cancers and is commonly found in tissue-invading parasites (Merdin et al 2016;Won et al 2015); VLM is often complicated by blood eosinophilia (Van Den Broucke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical and pathological aspects of VLMS are multifactorial and seem to be induced by the tissue damage caused by larvae migration. In addition, parasite-derived metabolites and the host inflammatory responses act in consonance to promote granuloma formation in several tissues, mainly in the lung and the liver ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The quilombola population in this study mostly (> 90.0%) reported no habits of consuming raw meat of either domestic or game animals, reducing the likelihood of toxocariasis via animal consumption. The ingestion of undercooked or raw meat from paratenic hosts, mainly cattle and chickens, has been associated with toxocariasis [ 58 60 ], mostly in Asian countries because of local habits of eating raw meat [ 61 ]. In Brazil, serosurveys and a review study [ 62 ] have indicated no association between consumption of raw meat and toxocariasis [ 13 , 53 , 63 ].…”
Section: Discussionmentioning
confidence: 99%